Genotypic Characterization of Orientia tsutsugamushi Isolated From Acute Encephalitis Syndrome and Acute Febrile Illness Cases in the Gorakhpur Area, Uttar Pradesh, India - Nanaware, Nikita; Desai, Dipen; Banerjee, Anwesha; Zaman, Kamran; Mittal, Mahim; Mittal, Mahima; Kulkarni, Smita (Frontiers in Microbiology, 2022)
Scrub typhus infections caused by Orientia tsutsugamushi (OT), continue to remain underdiagnosed globally, due to the lack of distinctive symptoms. The illusive nature of the AES outbreak in Gorakhpur, UP that claimed numerous pediatric lives was the driving force of this study which involved serological diagnosis (IgM-ELISA), isolation of OT in cell culture, confirmation by PCR and characterization by Sanger sequencing. Twelve out of 36 patients were seropositive, of which 4 were positive by PCR. Upon enrichment in cell culture, additional 3 patients (including two seronegative) were detected positive by PCR. Three of these 7 patients were found to be infected with two strains of OT. Taken together, this study for the first time reports occurrence of dual infections in addition to three circulating OT genotypes (Gilliam, Kato and Karp-like) and highlights the significance of enriching OT in cell culture system for efficient molecular detection.